Orally disintegrating tablets containing famotidine nanoparticles provide high intestinal absorbability via the energy-dependent endocytosis pathway - Nagai, Noriaki; Ogata, Fumihiko; Kadowaki, Reita; Deguchi, Saori; Otake, Hiroko; Nakazawa, Yosuke; Nagata, Mayumi; Sasaki, Hiroshi; Kawasaki, Naohito (Frontiers in Bioengineering and Biotechnology, 2023)
The permeability of the Biopharmaceutics Classification System (BCS) class III drugs are low, and their oral bioavailability needs to be improved. In this study, we attempted to design oral formulations containing famotidine (FAM) nanoparticles to overcome the limitations of BCS class III drugs. Dispersions containing FAM nanoparticles with a particle size of approximately 50–220 nm were produced by the bead-milling treatment. Moreover, we succeeded in preparing an orally disintegrating tablet containing FAM nanoparticles using the dispersions described above, additives (D-mannitol, polyvinylpyrrolidone, and gum arabic), and freeze-dry treatment (FAM-NP tablet). The FAM-NP tablet was disaggregated 3.5 s after addition to purified water, and the FAM particles in the redispersion of the FAM-NP tablet stored for 3 months were nano-sized (141 ± 6.6 nm). The in vitro intestinal penetration and in vivo absorption of FAM in rats applied with the FAM-NP tablet were significantly higher than those in rats applied with the FAM tablet containing microparticles. In addition, enhanced intestinal penetration of the FAM-NP tablet was attenuated by an inhibitor of clathrin-mediated endocytosis. In conclusion, the orally disintegrating tablet containing FAM nanoparticles improved low mucosal permeability and low oral bioavailability and overcame these issues of BCS class III drugs as oral formulations.